A new forest-dwelling Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodactylus) from Doi Suthep, Chiang Mai Province, northern Thailand - Kunya, Kirati; Panmongkol, Aumporn; Pauwels, Olivier S.g.; Sumontha, Montri; Meewasana, Jiraporn; Bunkhwamdi, Woraphot; Dangsri, Siriwat (Zootaxa, 2014)
We describe a new forest-dwelling Cyrtodactylus from Doi Suthep, Chiang Mai Province, northern Thailand. Cyrtodactylus doisuthep sp. nov. is characterized by a maximal known SVL of 90.5 mm; 19 or 20 longitudinal rows of dorsal tubercles; a continuous series of 34 or 35 enlarged femoro-precloacal scales, including six or seven pitted scales on each femur (male and females) separated by a diastema from six pitted (females) or pore-bearing (male) precloacal scales; no precloacal groove or depression; transversely enlarged subcaudal scales; and six or seven irregular thin beige dorsal bands between limb insertions.